ANALISIS TINGKAT PEMAHAMAN WAJIB PAJAK ORANG PRIBADI PADA PELAKSANAAN SELF ASSESMENT SYSTEM DALAM MELAKSANAKAN KEWAJIBAN PERPAJAKAN - SUPADMI, NI LUH; ANDRYANI, WIWIK (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 7 No 1 (2012), 2012)
This research aims to study individual tax payers’ understanding on self-assessment system implementation. Sample determining by purposive sampling method consists of 60 tax payers having printing business. Data are collected using questionnaire and interview. Then the data are analysed using descriptive statistics method. The result reveals that level of tax payers’ understanding is good.
Keywords: level of understanding, individual tax payer, self assessment system, tax obligation